Impact of preprocedural high-sensitive C-reactive protein levels on long-term clinical outcomes of patients with stable coronary artery disease and chronic kidney disease who were treated with drug-eluting stents. Issue 1 (July 2015) - Ogita, Manabu; Miyauchi, Katsumi; Kasai, Takatoshi; Doi, Shinichiro; Wada, Hideki; Naito, Ryo; Konishi, Hirokazu; Tsuboi, Shuta; Dohi, Tomotaka; Tamura, Hiroshi; Okazaki, Shinya; Daida, Hiroyuki
Abstract Background To evaluate the prognostic impact of preprocedural high-sensitivity C-reactive protein (hsCRP) levels on the long-term clinical outcomes after first-generation drug-eluting stent (DES) implantation in chronic kidney disease (CKD) patients with stable coronary artery disease (CAD). Methods and results We found significant interaction between CKD and hsCRP levels (p = 0.0138) in 1176 consecutive patients with stable CAD who were treated with first-generation DES implantation between 2004 and 2009 at our institution. Therefore, we separately analyzed data from patients with and without CKD who were assigned to tertiles based on preprocedural hsCRP levels. We evaluated the incidence of major adverse cardiovascular events (MACE) comprising all-cause death, nonfatal myocardial infarction, and target vessel revascularization after percutaneous coronary intervention during a median follow-up period of 1266 days. The rate of MACE significantly differed among the tertiles (log-rank p = 0.0074) in the group with CKD. Multivariate Cox regression analysis significantly associated a higher hsCRP tertile with MACE in the CKD group (hazard ratio 2.39, 95% confidence interval 1.27–4.75, p = 0.0062). Conclusion Elevated preprocedural serum hsCRP levels might be associated with the long-term clinical outcomes of patients with stable CAD and CKD who were implanted with first-generation DES.